La importancia de la auditoría de sistemas en el comercio electrónico (2023)
The article describes in a very general way the importance and benefits of carrying out a systems audit of e-commerce, which is exposed to new risks that affect organizations that chose to adapt to the system, this allowing cybercriminals to generate different methods of fraud and benefit from vulnerabilities, when these risks are detected, organizations are alerted with recommendations that they can implement to increase their security, It is explained how the ISO 19011:2018 guidelines for the audit of management systems allows the systems auditor to carry out an audit efficiently according to its principles, capabilities and requirements necessary to perform it, the article also highlights the growth that e-commerce has had in Colombia in recent years and the regulations that currently govern it, It is explained that systems auditing is a tool that is used to help e-commerce by evaluating the risks and controls that are part of information systems and how when carrying out these evaluations, recommendations arise to improve security, regulatory compliance, performance and user confidence